2018
DOI: 10.21037/atm.2017.07.28
|View full text |Cite
|
Sign up to set email alerts
|

Ground glass opacities management in the lung cancer screening era

Abstract: Pulmonary ground glass opacity (GGO) is becoming an important clinical dilemma in oncology as its diagnosis in clinical practice is increasing due to the introduction of low dose computed tomography (CT) scan and screening. The incidence of cancer in GGO has been reported as high as 63%. The purpose of this manuscript is to review best available evidence papers on management of GGO in lung cancer to address the following questions: (I) how to correlate CT findings with malignancy; (II) when and who operate? (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 32 publications
1
75
2
Order By: Relevance
“…Previous studies also suggested that an increase in size or solid component might predict a malignant tendency. 13,14 In our study, we did not observe a significant increase in size (P = 0.087). This might be because the follow-up time in our study was shorter than that in other studies, which were usually long-term studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies also suggested that an increase in size or solid component might predict a malignant tendency. 13,14 In our study, we did not observe a significant increase in size (P = 0.087). This might be because the follow-up time in our study was shorter than that in other studies, which were usually long-term studies.…”
Section: Discussioncontrasting
confidence: 64%
“…The GGO manifestation generally correlates with a lepidic, in situ, non-invasive growth pattern of cells along preexisting alveolar structures (4). A previous study has reported that GGO lung cancer may have several unique features, including an insignificant association with smoking history and a low degree of invasive biological characteristics (3). As the importance of GGO lung cancer is increasing, more researches have focused on the diagnosis and treatment of this early stage lung cancer; however, the epidemiology of lung cancer with GGO manifestation has not yet been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the introduction of low-dose computed tomography (CT) and screening procedures, the number of diagnoses of pulmonary ground glass opacity (GGO) lung cancer in clinical practice is increasing (1,2). The GGO manifestation is generally caused by local airspace filling as a result of inflammation or neoplastic proliferation, and some studies reported that the malignancy rate of GGO was 63%, which has a higher malignant potential than solid nodules (3,4). The GGO manifestation generally correlates with a lepidic, in situ, non-invasive growth pattern of cells along preexisting alveolar structures (4).…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic strategies depend on the subtype of adenocarcinoma classification. Patients with pre/MIA are more amenable to sublobar resection (wedge resection or segmentectomy) to preserve more pulmonary function to be able withstand further pulmonary resection if a second primary lung cancer develops in the future (15,16). However, patients with IA should more preferably undergo lobectomy (17).…”
Section: Introductionmentioning
confidence: 99%